Reduction in RF sheath rectification with insulating antenna enclosure walls. (1st August 2022) - Bal, G.; Compernolle, B.V.; Pribyl, P.; Martin, M.J.; Larson, J.; Carter, T.A.
Abstract: Radiofrequency (RF) sheath rectification is one of the most prominent deleterious effects associated with ion cyclotron range of frequencies (ICRF) heating in fusion plasmas. RF sheaths and associated effects, such as impurity generation and convective cell generation, need to be mitigated to ensure that ICRF is a viable option for heating in future fusion devices. Experiments were performed on the Large Plasma Device (LAPD) at UCLA to explore the effects of using electrically-insulating antenna enclosures on RF rectified sheaths. Three different enclosure side-wall materials were used, including copper, MACOR (electrically insulating), and MACOR over copper. In the case of the MACOR–copper side walls, the non-conductive MACOR material was exposed to the bulk plasma but a layer of copper was added below to allow for image currents to flow. All three of the experiments had similar plasma density, temperature, and background magnetic field. In the case of the copper enclosure, RF rectified potentials, many times the local electron temperature, and associated formation of convective cells were observed and reported Martin M. et al (2017 Phys. Rev. Lett. 119 205002). In the experiments with MACOR and MACOR–copper enclosures, RF rectification was significantly reduced. Additionally, these latter two experiments showed no evidence of convective cell formation. Although the results from the MACOR experiment are reminiscent of the results obtained in ASDEX-U with a three-strap antenna optimized to reduce image currents on the antenna limiters Bobkov V. et al (2016 Nucl. Fusion 56 084001), the MACOR–copper experiment seems to suggest that insulating plasma facing materials have at least an equally strong impact on reducing potential rectification.